Eclampsia at the university of Abuja teaching hospital: a ten-year review - Ayogu, Malachy Emeka; Omonua, Kate Ifeoma; Omonua, Kate Ifeoma; Ayogu, Miriam Chinelo; Ayogu, Miriam Chinelo (International Journal of Research in Medical Sciences, 2019)
Background: Worldwide, eclampsia remains one of the major causes of maternal and perinatal morbidity and mortality. Pre-eclampsia/eclampsia is a multisystem disease and despite extensive research, no definitive etiology has been identified. This disease therefore continues to pose a challenge in obstetric practice, especially in developing countries like ours. We therefore set out to determine the prevalence, associated factors, and outcome of eclampsia at the University of Abuja Teaching Hospital, Abuja, Nigeria. Methods: A descriptive retrospective review of cases of eclampsia managed at the University of Abuja Teaching Hospital, Abuja over a 10-year period. The case notes of these women were retrieved, and relevant data obtained included age, parity, booking status, type of eclampsia, gestational age at presentation, mode of delivery, maternal and perinatal outcome variables. Data was analysed using the statistical package for social sciences (SPSS Inc, Chicago) version 20 and outcome variables represented in simple percentages. Results: Of the 22,945 deliveries conducted during that period, 257 cases of eclampsia were managed, putting the prevalence of eclampsia at 1.12%. Of these, 90.5% were unbooked, 67.6% were primigravidae and 88.2% were below 30years of age. Antepartum eclampsia was the commonest form, occurring in 67.6% of the patients. Caesarean section was the mode of delivery in 82.2% of cases. Maternal and perinatal mortality were 4.6% and 11.1% respectively. Conclusions: Eclampsia is still a major cause of maternal and perinatal morbidity and mortality in our environment. One intervention to reduce its impact is education on the importance of antenatal care attendance. It’s also pertinent that this basic form of care be made more affordable and more easily accessible to those women who are socially disadvantaged.